MO281: Development of an Experimental Model of Haemodynamic Frailty Predisposing to Acute Kidney Injury. (3rd May 2022) - Diaz-Morales, Noelia; Sancho Martinez, Sandra M; Fuentes-Calvo, Isabel; María Baranda Alonso, Eva; Del Rio Hontañon, Marta; Martinez Salgado, Carlos; Lopez-Hernandez, Francisco J
Abstract: BACKGROUND AND AIMS: Frailty is a pre-morbid condition characterized by physiological decline and reduced physiological reserve leading to increased vulnerability to disease, especially common among older adults. Tissue and organ function is underpinned by effective haemodynamic regulation coping with everyday acute challenges and stressors. Impairment of the haemodynamic response may lead to tissue hypoperfusion and subsequent adverse events, such as acute kidney injury (AKI) and others. 'Haemodynamic frailty' defines a clinically silent condition characterized by a compromised haemodynamic reserve and impaired adaptive response to supervening circumstances (i.e. stressors such as drugs). Yet, frailty also offers a window of opportunity for disease prevention and health maintenance. Dehydration, hypertension and some drugs are important causes of haemodynamic frailty [1]. In this work, we aimed to develop a pre-clinical model of haemodynamic frailty, based on dehydration and hypertension, predisposing to AKI. METHOD: Three-month old male spontaneously hypertensive (SHR) rats were divided into four groups: (1) Control (CT): rats with ad libitum access to drinking water, receiving saline solution (0.9% NaCl, i.p.). (2) Cisplatin (CDDP): rats with ad libitum access to drinking water, receiving a sub nephrotoxic dose of cisplatin (2.5 mg/kg, i.p.). (3) Water deprivation (WD): rats with no access to drinking water during 48 h, receiving saline solution (0.9% NaCl, i.p.). (4) Water deprivation + cisplatin (WD + CDDP): rats with no access to drinking water during the 48 h previous to the cisplatin administration (2.5 mg/kg, i.p.). The dose of cisplatin had proved to be sub-nephrotoxic for normal rats in our previous studies [2]. 24-hour urine and tail vein blood samples were collected at basal state (B), 2 days after water deprivation (D0), and 4 days after cisplatin administration (D4, day of maximum kidney damage). Urine samples were analysed for volume (urinary flow), specific gravity, osmolality, and proteinuria (Bradford method). Haematocrit was calculated from blood samples and plasma was used to determine osmolality, concentration of creatinine (Jaffe reaction) and urea (Jung method). RESULTS: SHR rats with 48 hours of water deprivation showed a 10% weight loss, increases in haematocrit and plasma osmolality and a highly concentrated urine (with elevated levels of urine specific gravity and osmolality), which indicates a moderate to severe state of dehydration. No alterations in renal function were observed after water deprivation. Administration of cisplatin triggered significant increases in plasma creatinine, plasma urea and proteinuria, indicative of AKI, only in rats previously deprived of water for 48 h. All the parameters studied remained normal in cisplatin-treated rats without water restriction. Our results suggest that our experimental animal model, based on a combination of hypertension and dehydration, reproduces a state of haemodynamic frailty in which rats become predisposed to undergoing renal failure following exposure to stressors (e.g. a sub-nephrotoxic dose of cisplatin) that are harmless to haemodynamically competent rats. CONCLUSION: To our knowledge, this is the first experimental model of haemodynamic frailty predisposing to AKI. This model will allow us to further study mechanisms and biomarkers useful for diagnosis and stratification of haemodynamic frailty in order to develop strategies to prevent undesired health outcomes, including renal damage.